Desensitization Protocol Administered Successfully with interferon-?; 2a in a child with chronic hepatitis b infection - Kilic, M.; Dogan, Y.; Taskin, E.; Sen, Y.; Kalpaklioglu, A.F. (My University, 2010)
[Abstract Not Available]
Keywords: Angioedema; Child, Preschool; Clinical Protocols; Desensitization, Immunologic; Drug Hypersensitivity; Hepatitis B virus; Hepatitis B, Chronic; Humans; Interferon Alfa-2a; Interferon Alfa-2b; Male; Urticaria; alpha2a interferon; alpha2b interferon; antihistaminic agent; angioneurotic edema; article; case report; child; chronic hepatitis; clinical effectiveness; clinical protocol; desensitization; disease duration; disease severity; dose response; drug hypersensitivity; drug withdrawal; follow up; hepatitis B; human; male; preschool child; single drug dose; skin test; treatment duration; treatment outcome; urticaria